Linguagem do atrevimento : história oral de vida e de permanência escolar de mulheres jovens estudantes, da camada popular, do IFMT e a escrita de Carolina Maria de Jesus - Oliveira, Tatiane de (2024)
In times of accelerated, technological, virtual, individual and impatient life, eye-to-eye exchanges of experiences seem to be disappearing. In an attempt to counter this reality of modern everyday life, the objective of this thesis is to listen to the life stories and school stay of young students, from the popular classes, in the 3rd year of Secretariat Technical Education Integrated with High School, at the Federal Institute of Mato Grosso (IFMT), Cuiabá/Octayde Jorge da Silva campus. The objects of study are the narratives of memories of these women and in the literary work Quarto de Despejo: diário de uma favelada, by Carolina Maria de Jesus, which belongs to the autobiographical literary genre. The hypothesis is that temporalities interfere with intersectionality in the unfolding of the life trajectories and narratives of Carolina Maria de Jesus and the IFMT collaborators. With regard to memory, identities and narratives, some authors are: Benjamin (2012), Candau (2021), Halbwachs (1990) and Seligmann-Silva (2003; 2022), in relation to pedagogical practices: hooks (2017). The methodology is oral history, based on Meihy and Seawright (2021) and Portelli (1997; 2001; 2016). The analysis is interdisciplinary by Candido (2006) and the analysis categories are gender, race and class based on Saffioti (2015). Data collection is carried out through documentary consultation by Marconi and Lakatos (2011) and through oral history interviews. The result confirms the hypothesis and shows that there are many similar memories, even after the age of 60 on average, despite generational differences, in addition to showing that orality, through dialogue and listening, it is an important way for teachers to learn a little more about their students. Therefore, prepare yourself for strong revelations: hunger, fights, friendships, romances, separations, pregnancy, studies, hopes, dreams and boldness.